Degeneración hepatocerebral adquirida: una rara complicación neurológica de la cirrosis hepática - Catarina Medeiros; Rita Serras Jorge (Sociedade Galega de Medicina Interna, 2023)
Liver cirrhosis is a major cause of morbidity and mortality worldwide. It should be considered a multisystemic disease. Various neurological complications are associated with cirrhosis. We reported a 64-years-old woman with medical history of hepatic cirrhosis caused by Hepatitis B and Hepatitis C virus, Child-Pugh Score 8 (Class B), with portal hypertension, ascites suppressed with diuretics, esophageal varices and hypertensive gastropathy, that presents with seven months history of subacute-onset hand tremor and postural imbalance. Neurological examination showed bilateral extreme nystagmus, rest and kinetic hand tremor, doubtful Romberg test and slightly enlarged base gait. Dosage of ammonia was normal. MRI showed homogenously increased T1 signal within the basal ganglia (nucleus pallidus), with normal T2-weighted, associated to manganese accumulation. The diagnose of Acquired hepatocerebral degeneration was made. Acquired hepatocerebral degeneration is a rare and debilitating neurological syndrome, characterized by movement disorders and cognitive impairment in cirrhosis or portosystemic shunts. Bilateral hyperintensity in the globus pallidus on T1-weighted sequences, with normal T2-weighted are the most common abnormal finding. It is a consequence of manganese deposition in nucleus ganglia. Medical treatments are not effective. Liver transplantation showed good outcomes.